Islamic Management and Risk Management Applications in Pesantren Based on Waqf - Robbani, Muhammad Nabil; Fatwa, Nur (Santri: Journal of Pesantren and Fiqh Sosial, 2024)
Waqf-based educational institutions are currently still in the "low" category, according to Indonesia's National Waqf Index (IWN) report. In this case, pesantren is an educational institution that was mostly established with waqf assets and has recently experienced fairly good development; pesantren are also categorized as waqf-based schools and were established by nadzir to waqf managers, currently totaling 26.23% of the total number of schools in Indonesia. This waqf-based school still has shortcomings in its management, as seen from its small development. The relatively low number of the National Waqf Index (IWN) occurs because philanthropists currently do not see good results from waqf management. Of the various purposes for which waqf assets are allocated, pesantren is one of the choices for which nadzir can endow their assets. However, there are still many obstacles found in management, and in general, they must be overcome by waqf managers. The method of analysis in this research uses descriptive literature analysis and primary data from semi-structured interviews in the in-depth interview category. Moreover, the results of the analysis found various important principles and steps of risk management according to Islam. They included the benefits of risk management for waqf-based pesantren by applying Islamic management and risk management. The implementation uses the principles of Islamic management and applies the initial planning stages of risk management. Pesantren must also follow the development of government schools so that they can compete and walk together for the advancement of education.